2017
DOI: 10.1200/jgo.2015.002790
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Disease Risk Factors: How Relevant in African Men With Prostate Cancer Receiving Androgen-Deprivation Therapy?

Abstract: PurposeCardiovascular disease risk factors have been associated with androgen-deprivation therapy (ADT) in white and Hispanic populations. It is therefore relevant to determine if there exists a relationship between these parameters in the African population.Patients and MethodsThe design of the study was cross sectional. Prostate-specific antigen concentration, waist circumference, body mass index (BMI), lipid profile, glucose level, and insulin level were determined in 153 patients with prostate cancer and 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 45 publications
0
9
1
Order By: Relevance
“…ADT has been shown in other studies to increase measures of central obesity independent of the type of ADT, and central obesity is one of the first metabolic changes to occur. 46 , 47 This may be a result of the fact that testosterone deficiency caused by ADT results in decreased visceral adipose tissue lipolysis and accumulation of abdominal fat stores. 48 Previous studies have shown a correlation between overproduction of ROS and fat accumulation, which may lead to lipid metabolic pathway dysfunction through direct lipid peroxidation, thereby maintaining a vicious cycle that, if not checked, may encourage CaP recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…ADT has been shown in other studies to increase measures of central obesity independent of the type of ADT, and central obesity is one of the first metabolic changes to occur. 46 , 47 This may be a result of the fact that testosterone deficiency caused by ADT results in decreased visceral adipose tissue lipolysis and accumulation of abdominal fat stores. 48 Previous studies have shown a correlation between overproduction of ROS and fat accumulation, which may lead to lipid metabolic pathway dysfunction through direct lipid peroxidation, thereby maintaining a vicious cycle that, if not checked, may encourage CaP recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Essien et al 1 reported an interesting study, “Cardiovascular disease risk factors: How relevant in African men with prostate cancer receiving androgen-deprivation therapy?” We have a few questions regarding the study.…”
Section: To the Editormentioning
confidence: 99%
“…We thank Dhanushkodi 1 sincerely for his questions regarding our study, “Cardiovascular Disease Risk Factors: How Relevant in African Men with Prostate Cancer Receiving Androgen-Deprivation Therapy?” 2 In our facility, the gonadotropin-releasing hormone agonist used is goserelin. The dose administered is 3.6 mg every 28 days subcutaneously until the prostate-specific antigen (PSA) level is 0 ng/mL.…”
mentioning
confidence: 99%
“…Blood pressure was assessed in this study, and there was no significant difference ( P < .05) in the blood pressures of those receiving ADT and those not receiving ADT. 2 Our study was cross-sectional, so we did not follow up with those patients receiving ADT to see if they had any cardiovascular events. That is also why we do not have baseline values of glucose, lipid profile, and indices of obesity.…”
mentioning
confidence: 99%
See 1 more Smart Citation